Peran TIK dalam Meningkatkan Kreativitas Guru pada Proses Pembelajaran di SMA NW Mataram: A Case Study - Lalu Muhammad Maulana Malik Ibrahim; Mentari Tatsbita Rusyda; Mohammad Mustari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the role of Information and Communication Technology (ICT) in enhancing teacher creativity in the learning process at SMA NW Mataram. The study employed a qualitative approach with a case study design. The research was conducted at SMA NW Mataram during the second semester of the 2025/2026 academic year. The research participants consisted of teachers who actively utilized ICT in their teaching practices. Data were collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data collection, data condensation, data display, and conclusion drawing and verification. Data validity was ensured through source triangulation, technique triangulation, member checking, and prolonged engagement. The findings indicate that ICT plays a significant role in enhancing teacher creativity in the learning process. Teachers utilize various digital media, such as laptops, the internet, PowerPoint presentations, instructional videos, and learning applications, to create more innovative, engaging, and interactive learning experiences. The use of ICT also helps increase students’ motivation and participation in learning activities. In addition, ICT serves as a source of knowledge through computer-based learning at school and as a tool for developing students’ interests and talents. However, the implementation of ICT still faces several challenges, including limited infrastructure and facilities, differences in technological proficiency among teachers, and insufficient training in technology utilization. Therefore, school support is needed through the provision of adequate facilities and the enhancement of teachers’ digital competencies to ensure the optimal integration of ICT in the learning process.